Seleção de clones RB de cana-de-açúcar no litoral Sul da Zona da Mata de Pernambuco utilizando técnicas multivariadas - SILVA, Gheysa Coelho (2008)
The work had as aimed (1): to quantify the genetic divergence between seven varieties patterns and eleven clones sugar-cane RB through techniques united and multivariate with base in ten characters agroindustrial.; (2) to evaluate the relationships among the agronomic and technological characters about the productivity in cane and sugar, and to identify your direct and indirect effects, to aid the process of selection of clones RB of sugar-cane. The experiment was developed in the agricultural area in sugar mill Trapiche - Sirinhaém-PE, during the agricultural year 2005/2006. The experimental design was randomized blocks with four repetitions and eighteen genotypes constituted by seven varieties patterns. Were appraised in cane-plant for the agricultural production the characters NC, DC, AC, PMC and TCH. To determinate of the technological characteristics BC, PC, FIB, PUR and TPH were measured. The widespread distance of Mahalanobis was used as dissimilarity measure. Were considered the correlations, and they were made the trail analyses. Were applied the hierarchical method of medium connections (UPGMA) and the method of optimization of Tocher. The results evidenced that the methodology allows to identify genotypes of larger genetic divergence for use in programs of improvement of the sugarcane, allowing to suggest possible crossings between the most divergent clones and productive RB992542 and RB992558 with the variety SP79-1911 and of the clone RB992558 with the variety RB92579. The characters PC, TCH, BC and AC were the main ones decisive in the quantification of the genetic divergence. The characters PMC, AC and DC should be considered in the selection of clones RB seeking improvement in the sugarcane productivity, as well as TCH and PC they can be selected seeking increase of the productivity of sugar. Indirectly, the selection through height and diameter of stems makes possible efficient answer for improvement of the sugarcane productivity.